Evidence-based diagnostic algorithm for visceral leishmaniasis in Bangladesh - Salam, Md. Abdus; Huda, M. Mamun; Khan, Md. Gulam Musawwir; Shomik, Mohammad Sohel; Mondal, Dinesh (Elsevier Ireland Ltd, 2021)
Evidence-based diagnostic algorithm is highly recommended for the visceral leishmaniasis (VL). This crosssectional study was performed in Bangladesh to evaluate VL diagnostic tools including serology, buffy coat smear microscopy for LD body and various DNA-based techniques using buffy coat in 100 confirmed VL cases and 100 controls. The performance of tools against spleen smear (gold standard) was evaluated using kappa coefficient. Diagnostic precision and other inherent indicators were considered for index scoring (IS) of performance of tools using factor analysis. A diagnostic algorithm was formulated based on the IS and availability of the tools at different health care facilities of Bangladesh. A high level of agreement (kappa ≥ 0.80) was observed for all the diagnostic tools. The highest kappa coefficients were found for rK39 RDT and rK39 ELISA (0.95), followed by ssuRNA-PCR (0.94), Buffy coat smear (0.93), rK28 ELISA (0.92), rK28 RDT (0.89), LAMP (0.89), Mini-exon PCR (0.86), ITS1 (0.85), and ITS2 PCR (0.80). rK39 RDT was found to be the best diagnostic test (IS: 1.7) followed by rK28 RDT (IS: 1.5), buffy coat smear microscopy (IS: 0.5), rK39 & rK28 ELISA (IS: 0.3), ssuRNA-PCR (IS: -0.7) and LAMP, Mini-exon, ITS1, & ITS2 PCR (IS: -0.9). rK39 RDT has been proposed as the best option for primary health care facilities, while buffy coat smear microscopy was found to be a good adjunct for confirmation of serology-positive cases and proposed for secondary and tertiary facilities. ssuRNA-PCR or LAMP can be an alternate confirmation tool only applicable to the tertiary facilities.